Impacts of Mo application on biological nitrogen fixation and diazotrophic communities in a flooded rice-soil system - Ma, Jing; Bei, Qicheng; Wang, Xiaojie; Lan, Ping; Liu, Gang; Lin, Xingwu; Liu, Qi; Lin, Zhibin; Liu, Benjuan; Zhang, Yanhui; Jin, Haiyang; Hu, Tianlong; et al. (The Science of the total environment, 2019)
Molybdenum (Mo) deficiency in the farmland of China may limit biological nitrogen fixation (BNF), however, the impact of Mo application on BNF capacities and diazotrophic communities in rice-soil systems is unclear. In this experiment, treatments in a 6.7 atom% 15N2-labelling field-based growth chamber for 74 days and treatments in a 99 atom% 15N2-labelling microcosm experiment for 40 days combined with 16S rRNA gene sequencing and DNA-stable isotope probing (SIP) were used to investigate the impacts of Mo application on BNF and diazotrophic communities. Our results showed that under the condition that no nitrogen (N) fertilizer was applied, Mo application (500 g sodium molybdate ha−1) significantly increased N2 fixation in a rice-Inceptisol system, from 22.3 to 53.1 kg N ha−1. Mo application significantly increased the number of nifH gene copies and the relative abundance of cyanobacteria in both growth chamber and microcosm experiments. Among cyanobacteria, the relative abundances of the most abundant genera Leptolyngbya and Microcoleus were significantly increased by Mo application. 15N2-DNA-SIP further demonstrated that Leptolyngbya and Microcoleus incorporated 15N2. Mo application greatly increased BNF in Mo-deficient paddy field (≤0.068 mg kg−1) and stimulated the growth of cyanobacteria. These results indicated that Mo application in Mo-deficient paddy field could be a useful measure to increase soil N input under no N fertilization. [Display omitted] •Mo application enhanced N2 fixation in a rice-soil system under no N fertilization.•Mo application increased the number of nifH gene copies in paddy soil.•Mo application stimulated the growth of cyanobacteria in paddy soil.•Non-heterocystous cyanobacteria Leptolyngbya and Microcoleus were sensitive to Mo.